Design of a 128‐channel transceiver hardware for medical ultrasound imaging systems - Jayaraj Kidav; Perumal M. Pillai; Deepak V; Sreejeesh S. G (IET Circuits, Devices and Systems)
Abstract In this work, the design and development of a 128‐channel transceiver hardware for medical ultrasound imaging systems and research is presented. The proposed hardware solution integrates the analog front‐end (AFE) sections, high voltage transmit pulser sections, field programmable gate array (FPGA)‐based transmit beamforming and control logic, time gain compensation (TGC) and continuous (CW) Doppler functional circuits, and the necessary power supplies (high voltage (HV) and low voltage (LV)) into a single board. In addition, it integrates pervasive segments like power, clock tree sections, and power management and debugger logic. The developed transceiver solution helps to advance the research in medical ultrasound imaging techniques and technologies. To prototype an ultrasound imaging system, the developed hardware can be interfaced with a 128‐channel ultrasound transducer array and an FPGA‐based signal processing module. As the transceiver hardware is designed with commercially available chipsets, it provides the flexibility to programme the ultrasound AFE signal chain, transmit beamforming and the arbitrary transmit wave pattern. Besides, compared to the commercial open ultrasound research scanners, the flexibility to interface FPGA‐based signal processing module helps to investigate the performance of hardware realisation of various ultrasound signal processing algorithms. Moreover, the work realises a single‐board transceiver solution for multichannel ultrasound system fulfilment.